2013
DOI: 10.4103/0971-3026.116564
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of hepatocellular carcinoma with drug eluting microparticles (DC-Beads): CT evaluation of response to the treatment

Abstract: Background and Study Aims:Our aim was to assess the efficacy and tolerability of drug-eluting beads-transarterial chemoembolization (DEB-TACE) in the treatment of hepatocellular carcinoma (HCC), evaluating the response to the treatment after 1, 6, 12, and 24 months with multidetector computed tomography (MDCT) comparing European Association for the study of the Liver (EASL) and modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria.Materials and Methods:We enrolled 154 patients with uni- or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In another prospective, randomized study, DEBDOX TACE resulted in a better objective response than bland embolization with non-loaded bead (73.1% versus 55.9%, respectively) 10 . Similarly, Boatta and colleagues showed a 72% objective response rate in 154 patients treated with DEBDOX TACE 24 . In a study by Suk et al ., where CBCT after DEBDOX TACE was used to predict short-term tumor response according to mRECIST, objective response was achieved in 85.6% of patients (complete response 63.8%, partial response 21.8%), and objective response rates at one month after CBCT-guided TACE was also reported in a study by Loffroy et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another prospective, randomized study, DEBDOX TACE resulted in a better objective response than bland embolization with non-loaded bead (73.1% versus 55.9%, respectively) 10 . Similarly, Boatta and colleagues showed a 72% objective response rate in 154 patients treated with DEBDOX TACE 24 . In a study by Suk et al ., where CBCT after DEBDOX TACE was used to predict short-term tumor response according to mRECIST, objective response was achieved in 85.6% of patients (complete response 63.8%, partial response 21.8%), and objective response rates at one month after CBCT-guided TACE was also reported in a study by Loffroy et al .…”
Section: Discussionmentioning
confidence: 94%
“…With improved treatment efficacy and tolerance, DEBDOX TACE represents a major advancement in treatment of intermediate stage HCC 2 , 6 , 9 , 10 , 23 . In a recent prospective, randomized phase II study comparing cTACE with DEBDOX TACE, the DEBDOX TACE group showed a trend for a higher objective response rate than the cTACE group (51.6% versus 43.5%, respectively), together with better tolerability 8 , 24 . In another prospective, randomized study, DEBDOX TACE resulted in a better objective response than bland embolization with non-loaded bead (73.1% versus 55.9%, respectively) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…One was focused on the prognostic role of number of target lesions more than on that of response criteria [ 13 ]. Another study reported response and survival data at specific time point, so that it was not possible to extract the overall data [ 14 ]. In five works authors chose RECIST 1.0, RECIST 1.1 or volumetric RECIST version as comparator response criteria [ 15 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The treatment effects of DEB-TACE are usually evaluated with contrast-enhanced examinations,[23] and CE-US has also been reported to be useful for assessing the outcomes of DEB-TACE. [4] Another advantage of CE-US is that it can be performed repeatedly in patients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%